Empirical Evaluation of Preprocessing and Balancing Techniques Impact Across Algorithm-Vectorizer Combinations in Sentiment Classification - Motta, Nathanael; Souza, Ana Claudia Maria de; Silva, Carlo Marcelo Revoredo da; Rodrigues, Cleyton Mario de Oliveira (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2025)
This study systematically evaluates the individual impact of six commonly applied preprocessing techniques on sentiment classification performance using 14,224 Steam reviews. Each technique was assessed across four algorithms (SVC, Random Forest, TextBlob, VADER) and three vectorization approaches (TF-IDF, Count Vectorizer, Hashing Vectorizer). Results reveal significant variability in preprocessing effectiveness: four consecutive stages (HTML cleanup, emoji removal, number elimination, punctuation normalization) produced identical results, indicating redundancy for this corpus. Stop word removal and stemming showed mixed effects depending on algorithm-vectorizer combinations. Machine learning approaches demonstrated different sensitivity patterns compared to lexicon-based methods. SVC with TF-IDF showed consistent performance across preprocessing stages. These findings challenge assumptions about universal preprocessing benefits and emphasize the importance of empirical validation for specific domains and algorithm combinations.